DINAMIKA HUKUM DAN PERKEMBANGAN PERBANKAN ISLAM DI INDONESIA - Abdul Mujib (Al-Ahkam, 2013)
Almost all countries in the world including Indonesia give serious attention to the existence of Islamic banking that using religion approach in all activities and services. Institutional development it should be followed by the availability of legal basis, which is an established and clear. During the six years of its inception, the Islamic banking law stands with a very limited law basis, although the limitations of regulations have been describing aspects of sharia in Islamic banking for sure. The improvement of law is done by replacing Law No. 7 of 1992 by the Law No. 10 of 1998. This law has explicitly mention sharia aspects of Islamic banking, however Islamic banking regulation still governed together with conventional banking. The birth of Law 21 of 2008 became an important change for the development of Islamic banking. This law has given limits and a clear boundary line between Islamic banking and conventional banking in various aspects. The development of Islamic banking regulation are gaining its momentum with the enactment of Law No. 21 of 2008 concerning Islamic Banking. The strategic value of this law is increasingly opening up opportunities and legal certainty to accelerate the development of Islamic banks in the future